Stimulating Business Angels in the Czech Republic - World Bank Group (World Bank, Washington, DC, 2018)
This report provides a systematic assessment of business angel activities, and the ecosystem surrounding innovation finance, in the Czech Republic. Based on literature reviews, published data sources and local stakeholder interviews, the report distills findings related to the demand for and supply of risk investments, and offers policy recommendations for stimulating business angels. The report characterizes the Angel ecosystem as emerging with potential for growth. It is small both in terms of the number of investors and the amount invested. There appears to be a general lack of syndication of investments and concentration of investments in the capital (Prague) and in the information, communication, and technology (ICT) sector. On the demand side, a credible deal flow does exist, although it falls short of constituting a critical mass needed to support the development of the market. While issues in the local environment may affect the flow of angel investments, these are not insurmountable, based on the country’s competitive ranking on relevant global and European indicators. Finally, the report proposes a number of policy recommendations for enhancing business angel awareness and investments, including data collection and mapping of early stage market activities (short-term), creation of Czech National Angel Association (medium-term), and implementation of incentivization measures such as co-investment funds and tax incentives (long-term).